2014
DOI: 10.1002/eji.201344206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT6 during vaccination with formalin‐inactivated RSV prevents induction of Th2‐cell‐biased airway disease

Abstract: The pattern of immune response to a vaccine antigen can influence both efficacy and adverse events. Th2-cell-deviated responses have been implicated in both human and murine susceptibility to enhanced disease following formalin-inactivated (FI) vaccines for measles and RSV. In this study, we used the Th2-cell-deviated murine model of FI-RSV vaccination to test the ability of a dominant negative, cell-penetrating peptide inhibitor of STAT6 (STAT6 inhibitory peptide ( Keywords: Formalin-inactivated RSV vaccine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…The target cells through which STAT6‐IP mediated its inhibitory activity were poorly defined. Our subsequent studies and those of Michael et al. implicated DCs and macrophages in STAT6‐IP‐dependent inhibitory responses.…”
Section: Discussionsupporting
confidence: 90%
“…The target cells through which STAT6‐IP mediated its inhibitory activity were poorly defined. Our subsequent studies and those of Michael et al. implicated DCs and macrophages in STAT6‐IP‐dependent inhibitory responses.…”
Section: Discussionsupporting
confidence: 90%
“…Although we had shown that neonatal STAT6-IP exposure had beneficial effects in allergen-driven AHR, one of our concerns at the outset of the current experiments was that the STAT6-IP might inhibit the development of an effective immune response to RSV. Whereas we found similar viral titers in the lungs of all RSV-infected neonates, treated with peptide or not, RSV was undetectable in all adults previously exposed to RSV as neonates, similar to our findings in the FI-RSV vaccine model [23] (data not shown). Moreover, the IPR-R group also gained weight more rapidly after reinfection and produced equivalent cytokine profiles in lung homogenates and BALF, as well as intracellular staining of CD3 + T cells upon adult reinfection compared with the CPR-R and SALR-R groups.…”
Section: Discussionsupporting
confidence: 90%
“…STAT6-IP reduces Th2-biased airway inflammatory responses in OVA [21] and ragweed [22] models of allergic airways disease when given before allergen challenge. More recently, we have shown that STAT6-IP modulates pathogenic Th2 responses induced following RSV infection of mice previously exposed to the FI-RSV vaccine [23].…”
Section: Introductionmentioning
confidence: 99%
“…My results are in agreement with previous studies that demonstrate STAT6 and Th2-associated cytokines are mediators of pulmonary inflammation, mucus hypersecretion, and AHR in lung disease (331)(332)(333). Similarly, the inhibition of STAT6 signaling via administration of a STAT6 inhibitory peptide during FI-RSV immunization reduced lung inflammation, weight loss, and clinical illness following RSV challenge (334). The STAT6 inhibitory peptide may prove useful in application with other RSV vaccine candidates to inhibit a Th2-biased immune response.…”
Section: Evaluation Of Rsv Vaccine Candidates In a Murine Modelsupporting
confidence: 91%